Future of nuclear medicine- a review - Othman, Siti Amira; Abu Bakar, Nurul Fathihah; Nor Azman, Nor Farah Amirah; Jasrin, Nurin Saqinah (2018)
The development of nuclear medicine has led to an entire subset of extremely effective strategies in diagnosis and disease therapy. The emerging advancements in nuclear medicine are vast and diverse. Nuclear medicine tests and treatments involve the use of small amounts of radioactive material in order to diagnose and determine the severity of a variety of conditions and diseases. Basically, nuclear medicine involves the use of the latest scans and facilities such as magnetic resonance imaging, computed tomography scans and positron emission tomography which will find in many modern medical institutions today. One significant advantage of using nuclear medicine is the ability to make complex medical procedures simpler and safer for patients. With this technology, physicians and medical professionals are able to examine in great detail the most sensitive areas. All examinations can happen without subjecting patients to possibly dangerous and invasive procedures and surgeries. This medical technology has allowed the advancement of treatment options for patients suffering from serious illnesses, such as cancer, by way of radiation or chemotherapy. Physicians and healthcare providers were delighted with the introduction of nuclear medicine, as it has made more reliable with the quality of medical services provided by health facilities all around the world. Today health care professionals face many challenges in regulation and the practice of their respective professions. As a result, they are confronted with new skills and new ways of practicing in nuclear medicine area every day.